2015
DOI: 10.1039/c5ra05765e
|View full text |Cite
|
Sign up to set email alerts
|

Violet pigment production from liquid pineapple waste by Chromobacterium violaceum UTM5 and evaluation of its bioactivity

Abstract: Highlights 39• Liquid pineapple waste, a novel nutritious low cost growth medium. 40• Post-treatment of bacterial effluent for eco-friendly disposal. 41• Violet pigment stable at optimum conditions. 42• Violacein and deoxyviolacein isolated and characterized. 43• Crude violet pigment shows bioactivity. 44 • The first report on the production of violet pigment using liquid pineapple waste 45 medium. 46 47 48 Abstract 49 50 Synthetic pigments have been utilized in numerous industries including textile, cosmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 42 publications
3
31
0
Order By: Relevance
“…The antimicrobial activities of these two compounds have been extensively studied (Tables 1 and 2 ), particularly for violacein. It is historically recognized that very few Gram-negative bacteria are susceptible to violacein, data that is supported by independent groups in many recent studies [ 3 , 39 – 41 , 58 ]. The fact that violacein has been produced in recombinant strains of E. coli , as well as in Salmonella typhimurium VNP20009, Enterobacter aerogenes IAM1183 and Citrobacter freundii ACCC 05411, with no clear detriment to the growth or viability of these strains [ 59 – 62 ] supports this further.…”
Section: Violacein and Prodigiosin As Antimicrobialsmentioning
confidence: 88%
“…The antimicrobial activities of these two compounds have been extensively studied (Tables 1 and 2 ), particularly for violacein. It is historically recognized that very few Gram-negative bacteria are susceptible to violacein, data that is supported by independent groups in many recent studies [ 3 , 39 – 41 , 58 ]. The fact that violacein has been produced in recombinant strains of E. coli , as well as in Salmonella typhimurium VNP20009, Enterobacter aerogenes IAM1183 and Citrobacter freundii ACCC 05411, with no clear detriment to the growth or viability of these strains [ 59 – 62 ] supports this further.…”
Section: Violacein and Prodigiosin As Antimicrobialsmentioning
confidence: 88%
“…For instance, passion fruit consists of about 60% of inedible parts (FAO, ) and rambutan contains approximately 54% of peel and seed (Radha & Mathew, ), mango fruit have a high amount of peel (20–30%) and seed (10–15%) (Larrauri et al ., ; Abdalla et al ., ), and dragon fruit contains about 25% of peel and 8–8.6% of seed (Liaotrakoon et al ., ). Thus, valorisation of these by‐products is important and receives more attention as it is known that several nutritional and bioactive compounds are present in these fruit by‐products such as pigments, organic acids, antioxidants and fibresAguilar et al ., ; Aruldass et al ., ; Martínez et al ., ). Moreover, other properties such as antimicrobial and enzyme inhibitory properties of phenolic compounds in fruit by‐products were discussed in recent reviews (Sekar et al ., ; Ademosun et al ., ; Oliveira et al ., ; Kong et al ., ; Melgar et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated VIO action on S. aureus , with a MIC of 7·8 μ g ml −1 and 15·6 μ g ml −1 for methicillin‐sensitive and resistant strains, respectively, whereas for Gram‐negative bacteria, the observed MIC was much higher, 125 μ g ml −1 for Pseudomonas aeruginosa and 1000 μ g ml −1 for Klebsiella pneumoniae (Aruldass et al . ).…”
Section: Discussionmentioning
confidence: 97%